Sektor Unggulan Kota dan Kabupaten di Provinsi Jawa Timur - Nurul Azizah Az zakiyyah; Ratih Herliana (Jurnal Ekonomi-Qu, 2023)
This research is entitled "Analysis of the Leading Economic Sector in East Java Province" with the aim of knowing the superior and non-superior sectors, comparing and analyzing changes in the growth of the economic sector in East Java Province in 2016-2020. The analysis method uses the Lacotion Quotient analysis, Growth Ratio Model and Shift Share using Microsoft Excel as an analytical tool. The results of the analysis show that other service sectors are the basis in 28 regencies/cities and Tuban Regency is the district that has the most leading sectors and is suitable for better development with 17 leading sectors. Sectors that have the potential to be developed, namely the information and communication sector, education services as well as health services and social activities are sectors that experience the most potential or high sector growth both in the reference area or study area. Shift-Share analysis shows that the economy of the Regency/City indicated to experience significant growth as a result of the competitive advantage, namely the Regencies of Sumenep, Lumajang, Jember, Lamongan and Pamekasan.